Workforce Management Based On Charity in Muslim Organizations - Dadach, Zin-Eddine (International Journal of Islamic Business & Management, 2020)
Islamic literature highlights eight major functions of Islamic HRM; namely HR planning, recruitment, selection, orientation, performance appraisal, training and development, compensations and benefits, and career development. The objective of this paper is to consider the Divine Science of Charity as it applies to organizations as a form of workforce management. Firstly, in order to properly apply the divine laws of charity in any hierarchy, every employee should be allocated to a position correlating to their skill level. In addition, if everyone in the company is willing to please Allah (SWT) by helping personnel under supervision (muʿāmalāt), it will result in minimum friction between employees, meanwhile boosting the morale and engagement of all personnel. This will result in the maximized efficiency of the workflow at each level of the organization. Moreover, the reward for charity–leaders is happiness, which will allow them to create an enjoyable environment in the workplace. For the 2nd divine law of charity, each member of the company will be able to self-purify their soul and add the workflow as good deeds in the Eternal Path of Charity.